Chamling basic vowels: acoustic analysis - Rai, Bhabindra Kumar (Gipan, 2019)
This study analyzes Chamling vowels acoustically. Fundamental and formant frequency values of the vowels have been measured for both the male and female speakers and their individual values have been calculated for the comparison. Then, the average values have been computed for the specification of the vowels through the acoustic measurement. Acoustic properties have been observed in terms of gender, age, conditioning environment and intrinsic values. All this has clearly been presented in tables and figures. The study covers an overall acoustic description of the Chamling vowels on the basis of sound spectrogram using the up-to-date Pratt software. On the whole, it is concerned with phonetic study of the Chamling vowels in terms of acoustic properties and articulatory strategies.